Analisis Laju Pertumbuhan dan Efektivitas Penerimaan Retribusi Pengujian Kendaraan Bermotor pada Dinas Perhubungan Kabupaten Malang - Rizkya Noviana Romadhona; R.M Mahrus Alie; Angguliyah Rizqi Amaliyah (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to analyze the growth rate and effectiveness of motor vehicle testing levy revenues at the Malang Regency Transportation Agency during the period 2020 to 2024. The approach used is quantitative descriptive with data collection techniques in the form of secondary documentation and direct interviews with related parties. The results of the study show that the average growth rate of levy revenues reached 6.83%, which is included in the positive growth category and is classified as